2019
DOI: 10.21873/invivo.11650
|View full text |Cite
|
Sign up to set email alerts
|

Phase Angle as an Objective and Predictive Factor of Radiotherapy-induced Changes in Body Composition of Male Patients With Head and Neck Cancer

Abstract: Background: Unfavorable changes in body composition are frequent among patients with head and neck cancer (HNC). Unfortunately, in daily clinical practice, there is a lack of reliable diagnostic tools for predicting changes in body composition in individuals following radiotherapy (RT). Among non-invasive tools, bioelectrical impedance analysis (BIA) seems to be most promising. One BIA parameter, the phase angle (PA), reflects condition of various body cells and their mass in detail. Materials and Methods: Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
2
7
0
2
Order By: Relevance
“…(30) Besides perioperative complications, studies focused on head and neck cancer patients have also showed correlation of BIA parameters with prolonged hospital stay(31), survival rates(9, 10, 32), and radiotherapy outcomes. (33)…”
Section: Discussionmentioning
confidence: 99%
“…(30) Besides perioperative complications, studies focused on head and neck cancer patients have also showed correlation of BIA parameters with prolonged hospital stay(31), survival rates(9, 10, 32), and radiotherapy outcomes. (33)…”
Section: Discussionmentioning
confidence: 99%
“…[ 42 ] Whereas a higher PA suggests large quantities of intact healthy cells. [ 43 ] HNC Patients with low PA prior to chemoradiotherapy treatment are more susceptible to significant weight loss and muscle wasting during cancer treatment in contrast to those with normal PA values. Hence, high risk of low survival.…”
Section: Discussionmentioning
confidence: 99%
“…The currently available predictive tools-the patient's clinical features (age, smoking, and socioeconomic status), anthropometric measures (body weight, and BMI), clinical scales (Nutritional Risk Score-NRS-2002), or laboratory tests (markers of inflammation and the albumin level)-are insufficient for predicting the development of malnutrition during RT [54,67,81,[89][90][91]. The more reliable tools for the prediction of RTinduced changes in body composition demonstrate parameters derived from BIA, mainly the phase angle (PA), whose value is decreased in malnourished/cachectic patients [92]. For cachexia and sarcopenia detection, the most reliable tools are computed tomography (CT) and DXA [90,91].…”
Section: Prediction Of Nutritional Deficiencies Developing During Thementioning
confidence: 99%
“…Phase angle (PA) [52] The risk of malnutrition/cachexia developing during CRT increased by 1.71 per mean PA decrease by one unit PA [92] Patients with low PA had 9.3-fold higher chance of BMI reduction below 18.5 kg/m 2 and over 5.9-fold and 4.2-fold higher chance of lean mass (LM) and FM reduction after therapy end compared with patients with a high PA value pre-albumin [81] Decrease of > 15% in pre-albumin level was more likely to be malnourished (OR = 2.442) after RT commencement. Pre-albumin level predicts weight loss during RT pre-albumin [83] The percentage of weight loss during RT negatively correlated with pre-albumin concentration, but not with other nutrition parameters 3-hydroxybutyrate (3HB) [102] 3HB is a relatively sensitive marker that allows earlier identification of the HNC at higher risk of > 10% weight loss during RT/CRT TNF-α−1031T/C [103] Patients with CC genotype had a significantly higher chance of BMI decrease < 18.5 kg/m 2 (underweight) following RT (OR = 23.0) and lower total protein and albumin concentration in the blood compared to carriers of CT and TT genotypes SELP-2028 C/T [104] The chance of losing ≥ 10% body weight and the development of cachexia during radical RT in patients with CC and CT genotypes was five times higher than TT genotype carriers (OR = 5.0)…”
Section: Tool/marker Role In Prediction Of Rt-induced Nutritional Defmentioning
confidence: 99%